Ethnomedicinal plant wealth of different regions of Uttar Pradesh: Integrating traditional knowledge into healthcare - Supriya Kumari SHARMA; Prachi BALIYAN; Afroz ALAM (Nova Geodesia)
This study explores the ethnomedicinal practices and plant diversity in various regions of Uttar Pradesh, India, focusing on the traditional knowledge and utilization of medicinal plants by local tribal communities. A comprehensive review of relevant literature was conducted using academic databases to document the floristic diversity and indigenous applications of ethnomedicinal plants in the North-Eastern Terai Region, Jaunsar-Bawar Hills, Saharanpur, and Sonaghati of Sonbhadra district. The study identified 111 plant species from various genera and families, with Fabaceae, Acanthaceae, Solanaceae, Malvaceae, Euphorbiaceae, and Asteraceae being the most frequently employed in traditional healing practices. The most often utilized plant parts were the leaves, which were followed by the bark, roots, and other botanical parts. The knowledge of herbal applications is deeply rooted in cultural traditions and transmitted through generations by traditional healers and medicinal practitioners who play a crucial role in preserving their ancestral heritage. The study also highlights the diverse methods employed by plant healers to harness the therapeutic properties of medicinal plants, including making pastes, extracting juice, preparing decoctions, using powdered forms, and applying raw leaves. The findings emphasize the importance of documenting and conserving the rich ethnomedicinal knowledge and plant resources in Uttar Pradesh, promoting sustainable utilization and preservation of cultural practices for future generations.